Ultization of Radiological Techniques in Early Diagnosis of Lunc Cancer - Sisi Yulianti; Budiman, M A rif; Miftachul Amri (AKADEMI TEKNIK ADI KARYA, 2024)
Lung cancer remains a leading cause of mortality worldwide, underscoring the critical need for early detection to improve patient outcomes. Radiological techniques play a pivotal role in the timely diagnosis of lung cancer, offering non-invasive approaches that facilitate early intervention and treatment planning. This paper comprehensively reviews the utilization of radiological modalities, including computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET), and chest X-ray, in the early detection of lung cancer. Emphasizing the significance of each modality in identifying suspicious pulmonary nodules, characterizing lesions, and staging disease progression, the review highlights advancements in imaging technologies that enhance sensitivity and specificity. Furthermore, it addresses challenges such as false positives, radiation exposure, and cost-effectiveness, proposing strategies to mitigate these limitations. The review also explores emerging trends such as artificial intelligence (AI) algorithms and molecular imaging techniques, which hold promise for further improving diagnostic accuracy and personalized treatment approaches. By synthesizing current evidence and future directions in the utilization of radiological techniques for early lung cancer diagnosis, this review contributes to advancing clinical practice and ultimately reducing the burden of lung cancer morbidity and mortality.